1982
DOI: 10.1111/j.1471-0528.1982.tb04643.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral venous concentrations of oestrogens in postmenopausal women with ovarian cancer

Abstract: Serum concentrations of oestrone, oestradiol and oestriol were measured in 23 postmenopausal women, 12 with ovarian cancer and 11 with genital prolapse. Oestrone (387.6 pmol/l) and oestradiol(72.7 pmol/l) levels were higher in the cancer group than those in the control group (159-8 and 27.5 pmolil respectively), while oestriol levels did not differ (434.5-270-8 pmolil). T h e results indicate abnormal ovarian function in postmenopausal patients with ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 9 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Indeed, ICI plus P4 cotreatment induced more cell loss and higher caspase 3 activity in OVCA cells than P4 alone. Clinically, it has been reported that epithelial OCas produce estrogens (Heinonen et al, 1982;Taube et al, 2002), although we have not established whether estrogens are produced by the OVCA cell lines. On the contrary, P4 promoted cell growth and ICI induced apoptosis in MCF-7 cell cultures.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, ICI plus P4 cotreatment induced more cell loss and higher caspase 3 activity in OVCA cells than P4 alone. Clinically, it has been reported that epithelial OCas produce estrogens (Heinonen et al, 1982;Taube et al, 2002), although we have not established whether estrogens are produced by the OVCA cell lines. On the contrary, P4 promoted cell growth and ICI induced apoptosis in MCF-7 cell cultures.…”
Section: Discussionmentioning
confidence: 88%
“…Few studies have surveyed the hormonal profiles in the peripheral circulation of patients with ovarian cancer. When this has been determined, the results have not been correlated with receptor status (Jeppsson et al 1982;Heinonen et al 1982;Waxman 1984). The data from this pilot study of 53 subjects, in whom the peripheral circulating hormone concentrations and the corresponding steroid receptor content were available, are limited by several factors.…”
Section: Toppilaetalmentioning
confidence: 92%
“…The presence in ovarian cancer cells of receptors for oestrogen and progesterone (Holt et al, 1979;Rowland et al, 1985;Sutton et al, 1986), and for androgens (Hamilton et al, 1981), combined with the ability of these cells to synthesise steroid hormones (Heinonen et al, 1982;Backstrom et al, 1983), suggests that hormonal manoeuvres may be useful in the treatment of this condition.…”
mentioning
confidence: 99%